Działalność Milicji Obywatelskiej w Łodzi (sierpień 1914 – lipiec 1915 r.) - Stawiszyńska, Aneta (Acta Universitatis Lodziensis. Folia Historica, 2015)
After leaving the city by the tsarist administration in the first weeks of the war, custody order took over the structure of organized spontaneously, the Civic Militia (MO). Łódź was divided into so-called. MO areas, which in turn were divided into so-called uczastki. One of the first tasks of a supervising public buildings in the city and on the protection of the local trees regularly robbed by fuel-free population. With time MO expanded his powers. With MO were many sections responsible for specific aspects of city life, eg. issues order, health and the fight against prostitution. Of particular importance was functioning as the Section on Legal Affairs and the Committee on reconnaissance conciliation, interim justice. After the town was captured by the German army in December 1914 MO was forced to implement regulations occupier. In January, 1915 MO was reorganized as a result, the positions remained only 1000 militiamen who received salaries since then. The militia was disbanded at the end of June 1915. One of the reasons were frequent conflicts MO with representatives of the occupation authorities. In place of MO was appointed Imperial Police Office. Despite the undeniable fraud and irregularities, MO activity has contributed to the development of civic awareness Lodzians.